A Spectroscopic Study of Brazilwood Paints in Medieval Books of Hours. Issue 4 (April 2014) - Melo, Maria João; Otero, Vanessa; Vitorino, Tatiana; Araújo, Rita; Muralha, Vânia S.F.; Lemos, Ana; Picollo, Marcello
In this work, microspectrofluorimetry was for the first time applied to the identification of the red organic lakes that are characteristic of the lavish illuminations found in 15 th century books of hours. Microspectrofluorimetry identified those red paints, ranging from opaque pink to dark red glazes, as brazilwood lakes. An unequivocal characterization was achieved by comparison with reference paints produced following recipes from the medieval treatise The Book on How to Make Colours, and was further confirmed by fiber optic reflectance spectroscopy (FORS). For these treasured cultural objects, microspectrofluorimetry and FORS proved to be the only techniques that could identify, in situ or in microsamples, the chromophore responsible for the pinkish hues: a brazilein-Al 3+ complex. Additionally, a multi-analytical approach provided a full characterization of the color paints, including pigments, additives, and binders. Microspectroscopic techniques, based on infrared and X-ray radiation, enabled us to disclose the full palette of these medieval manuscripts, including the elusive greens, for which, besides malachite, basic copper sulfates were found; Raman microscopy suggested a mixture of brochantite and langite. Infrared analysis proved invaluable for a full characterization of the additives that were applied as fillers or whites (chalk, gypsum, and white lead) as well as the proteinaceous and polysaccharide binders that were found pure or in mixture.